Industrial Halal Blockchain: The Great Potential of The Digital Economy in Indonesia - Asnawi, Nur; Danila, Nevi; Moch Mahsun (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
The development of the digital economy is an essential part of Indonesia's G20 presidency. We evaluate the digital economy, focusing on blockchain adoption in the financial services industry and buying and selling transactions. Even then, there are still doubts regarding system transformation, information security, and guarantee of traceability, both in terms of data validation in complying with Islamic principles (halal industry). In this issue, we show that the importance of developing blockchain adoption can be developed in the broader field, especially in responding to deindustrialization on the principles of collaboration in digital transformation that are more inclusive, empowering, complying with sharia principles, and sustainable. This research is critical to know as a basis for consideration by government policies, industry, and entrepreneurs in considerations related to blockchain adoption through supply chain management principles that are standardized with the principles of the halal industry.